PH-dependent bioavailability, speciation, and phytotoxicity of Tungsten (W) in Soil Affect Growth and Molybdoenzyme Activity of Nodulated Soybeans - Oburger, Eva (2018)
Increasing use of tungsten (W)-based products opened new pathways for W into environmental systems. Due to its chemical alikeness with molybdenum (Mo), W is expected to behave similarly to its "twin element", Mo; however, our knowledge of the behavior of W in the plant-soil environment remains inadequate. The aim of this study was to investigate plant growth as well as W and nutrient uptake depending on soil chemical properties such as soil pH and texture. Soybean (Glycine max cv. Primus) was grown on two acidic soils differing in soil texture that were either kept at their natural soil pH (pH of 4.5-5) or limed (pH of ≥7) and amended with increasing concentrations of metallic W (control and 500 and 5000 mg kg-1). In addition, the activity of molybdoenzymes involved in N assimilation (nitrate reductase) and symbiotic N2 fixation (nitrogenase) was also investigated. Our results showed that the risk of W entering the food web was significantly greater in high-pH soils due to increased solubility of mainly monomeric W. The effect of soil texture on W solubility and phytoavailability was less pronounced compared to soil pH. Particularly at intermediate W additions (W 500 mg kg-1), symbiotic nitrogen fixation was able to compensate for reduced leaf nitrate reductase activity. When W soil solution concentrations became too toxic (W 5000 mg kg-1), nodulation was more strongly inhibited than nitrogenase activity in the few nodules formed, suggesting a more-efficient detoxification and compartmentalization mechanism in nodules than in soybean leaves. The increasing presence of polymeric W species observed in low-pH soils spiked with high W concentrations resulted in decreased W uptake. Simultaneously, polymeric W species had an overall negative effect on nutrient assimilation and plant growth, suggesting a greater phytotoxicity of W polymers. Our study demonstrates the importance of accounting for soil pH in risk assessment studies of W in the plant-soil environment, something that has been completely neglected in the past.